The Unprecedented Omicron Surge in Hong Kong: A More Natural or More Man-Induced Tragedy? - Fung Kei Cheng (Athens Journal of Health and Medical Sciences)
COVID-19 infection control in Hong Kong was effective through strict antipandemic measures in the first four waves beginning in 2020, although it hurt not only physiological and psychological health but also social and economic activities. However, there was an uncontrollable boom in local Omicron cases and deaths from late January 2022, particularly among the senior population. Epidemiologists bemoaned the low vaccination rate among older adults which attributed to the rapid contagion. This analysis looks into a nexus of causes, and discusses the roles of manpower, medical resources, management, healthcare policies, and the balance between anti-pandemic tactics and individual health. Fundamentally, trust in the government is indispensable to success in combating public health disasters. Medical veterans urge a comprehensive inquiry in order to improve the healthcare system and hence cope with future infectious diseases, which authorities should respond to positively and promptly.